Development of Universal Indicator from Organic Waste Material - Maria Bestanika Nugrahani; Risnita Vicky Listyarini (Postgraduate, University of Mataram, 2023)
This research aims the development of universal indicators from organic waste materials. This is a research and development (R&D) with a modified ADDIE model. The universal indicator developed was implemented for students of class XI MIPA at Senior High School in Bantul, Yogyakarta. The data collection methods used are interviews, product validation sheets, observations, tests, and questionnaires. The results showed that the universal indicator can determine a pH value of 0-14 and can be stored for 11 days. The product developed has met valid criteria with an average percentage obtained of 94.20% based on validators evaluation. The product developed has met effective criteria with an average percentage obtained of 95.00% based on students’ science skills and 75.00% based on student learning outcomes and practical criteria with an average percentage obtained of 87.40%.